2019
DOI: 10.1093/jas/skz175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gestation dietary methionine/lysine ratio on placental angiogenesis and reproductive performance of sows1

Abstract: The current study aims to evaluate the effects of different gestation dietary Met/Lys (methionine, Met/lysine) ratios on the production performance of sows. Specifically, it measured the effect of Met on plasma urea and AA concentrations and placental vascular density of pregnant sows. A total of 325 multiparous sows (third parity, Large × White) were randomly allocated to five dietary treatments (n = 65) with five dietary Met/Lys ratios 0.27 (nutrient requirements of swine [NRC] 2012 level), 0.32, 0.37, 0.42,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…In modern animal production, gestational restriction feeding is an effective and widely used practice to improve the reproductive performance of sows. Our previous study found that under the restriction feeding conditions, increasing the Met/Lys ratio from 0.27 to 0.37 can significantly increase the average pig birth weight and the litter weight in the pigs that are born alive [6]. However, when Met/Lys ratio was further increased to 0.47, the rate of piglets with a weight <0.9kg increased and the placental vascular density decreased significantly [6].…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…In modern animal production, gestational restriction feeding is an effective and widely used practice to improve the reproductive performance of sows. Our previous study found that under the restriction feeding conditions, increasing the Met/Lys ratio from 0.27 to 0.37 can significantly increase the average pig birth weight and the litter weight in the pigs that are born alive [6]. However, when Met/Lys ratio was further increased to 0.47, the rate of piglets with a weight <0.9kg increased and the placental vascular density decreased significantly [6].…”
Section: Discussionmentioning
confidence: 96%
“…Our previous study found that under the restriction feeding conditions, increasing the Met/Lys ratio from 0.27 to 0.37 can significantly increase the average pig birth weight and the litter weight in the pigs that are born alive [6]. However, when Met/Lys ratio was further increased to 0.47, the rate of piglets with a weight <0.9kg increased and the placental vascular density decreased significantly [6]. In this study, the maternal plasma at E114 d and the placental H 2 S concentrations were consistent with the sows' reproductive performance.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations